Drug Induced Pneumonitis Secondary to Treatment with Paritaprevir/Ritonavir/Ombitasvir and Dasabuvir (VIEKIRA PAK®) for Chronic Hepatitis C: Case Report of an Unexpected Life-Threatening Adverse Reaction - Shih Yea Sylvia Wu; Bridget Faire; Edward Gane (Case Reports in Medicine)
VIEKIRA PAK (ritonavir-boosted paritaprevir/ombitasvir and dasabuvir) is an approved treatment for compensated patients with genotype 1 (GT1) chronic hepatitis C virus (HCV) infection. This oral regimen has minimal adverse effects and is well tolerated. Cure rates are 97% in patients infected with HCV GT 1a and 99% in those with HCV GT 1b. We report the first case of life-threatening allergic pneumonitis associated with VIEKIRA PAK. This unexpected serious adverse event occurred in a 68-year-old Chinese female with genotype 1b chronic hepatitis C and Child-Pugh A cirrhosis. One week into treatment with VIEKIRA PAK without ribavirin, she was admitted to hospital with respiratory distress and acute kidney injury requiring intensive care input. She was initially diagnosed with community acquired pneumonia and improved promptly with intravenous antibiotics and supported care. No bacterial or viral pathogens were cultured. Following complete recovery, she recommenced VIEKIRA PAK but represented 5 days later with more rapidly progressive respiratory failure, requiring intubation and ventilation, inotropic support, and haemodialysis. The final diagnosis was drug induced pneumonitis.